Pengaruh Online Customer Review dan Harga terhadap Keputusan Pembelian Pakaian pada Shopee di Kota Medan - Dhafa Fadillah; Jumjuma Jumjuma; Annalisa Sonaria Hasibuan; Anggiat P. Simbolon (Universitas 45 Surabaya, 2024)
The presence of internet technology has changed people's lifestyle patterns, including people's shopping patterns, where previously buying and selling transactions were carried out face to face, now transactions can be accessed just by using a smartphone. The aim of this research was to examine the influence of online customer reviews and prices on clothing purchasing decisions at Shopee e-commerce in Medan City. This research is motivated by the differences between online purchases and offline purchases in assessing a product. The type of research used in this research is quantitative research and uses incidental sampling as the sampling technique. Testing was carried out using SPSS 25. The results of data analysis showed that: 1) online customer reviews had a positive and significant effect on the decision to purchase clothes at Shopee among the people of Medan City. This can be seen from the results of the partial hypothesis test (t-test), where tcount > ttable (9,045 > 1,986) and the significance value is 0.000 < 0.05. 2) price has a positive and significant effect on purchasing decisions among the people of Medan City in purchasing clothes in Shopee. This can be seen from the results of the partial hypothesis test (t-test), where tcount > ttable (5.760 > 1.986) and significant, namely 0.000 < 0.05. 3) simultaneous regression testing (F test) on the online customer review and price variables. shows that it simultaneously has a positive and significant effect on clothing purchasing decisions among the people of Medan City when purchasing via e-commerce Shopee, this can be seen from the results of the simultaneous test (F Test), where Fcount > Ftable (318,682 > 3.094) and the significance is 0.000 < 0.05.4) the coefficient of determination (R2) is 0.870 , so it can be concluded that 87% of the online customer review and price variables have an influence on clothing purchasing decisions at Shopee in Medan City, while the remaining 13% is influenced by other variables not examined in this study.